Villous adenoma of the renal pelvis: a common entity at an uncommon location - Sushma Bharti; Vikarn Vishwajeet; Himanshu Pandey; Poonam Abhay Elhence (University of São Paulo, 2021)
Villous adenoma is uncommonly seen in the urogenital tract and is even more rarely seen in the upper urinary tract and renal pelvis. Like colorectal adenomas, these neoplasms can transform into adenocarcinoma. The preoperative diagnosis is challenging due to their frequent association with hydronephrosis. Herein, we present the case of a villous adenoma of the renal pelvis in a 62-year-old man presenting with recurrent urinary tract infection. The computed tomography scan showed marked hydronephrosis but no suspicious mass in the right kidney. A laparoscopic right nephrectomy was performed. Gross examination revealed a dilated renal pelvis with an irregular exophytic lesion in the renal pelvis's upper surface. The histopathological examination showed slender, elongated villi with thin fibrovascular cores, consistent with villous adenoma morphology. Isolated villous adenomas have a favorable prognosis. However, the pathologist should undertake a search for an invasive component.